Energy Down-Conversion Cs3Cu2Cl5 Nanocrystals for Boosting the Efficiency of UV Photodetector - Liu, Chengjun; Wang, Lixi; Fang, Fan; Zhao, Zihan; Pan, Jiangyong; Akram, Javed; Shafie, Suhaidi Bin; Talaighil, Razika Zair; Li, Qing; Zhao, Zhiwei; Wu, Jun; Zhu, Zhuoya; et al. (Frontiers in Materials, 2021)
Zero-Dimension (0D) lead halide perovskite nanocrystals (NCs) have attracted a sight of interest in the field of optoelectronic devices due to their outstanding properties, such as high photoluminescence quantum yield (PLQY), size- and composition-controlled tunable emission wavelengths. However, the toxicity of lead (Pb) element in the lead perovskite NCs is the bottleneck for the commercial application of perovskite NCs. Herein, we report a facile ligand–assisted synthesis to achieve lead-free Cs3Cu2Cl5 NCs with high PLQY of ~70% and good stability against environmental oxygen/moisture as a promising down-conversion material. It has good merits of high PLQY and large Stokes Shift (~300 nm) originated from the effect of Jahn-Teller distortion and self-trapped excitons (STEs). Furthermore, the Cs3Cu2Cl5 NCs embedded composite films (NCCFs) were utilized to enhance the ultraviolet (UV) response of silicon (Si) photodetectors. External quantum efficiency (EQE) measurements show that the UV response can be greatly improved from 3.3% to 19.9% @ 295 nm based on NCCFs combined with Si photodiodes. Our work offers an effective approach to develop highly efficient and stable lead-free Cs3Cu2Cl5 NCs for the application in the solar-blind UV photodetector.